Sharing Economy – Concept, Origins and Potential - Sztokfisz, Barbara (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The paper presents a theoretical overview of definitions of the sharing economy. It emphasises the role of the access to goods and services, which are systematically taking the place of ownership. It refers to the main categorizations presented in the literature as well as the genesis of the concept. It presents the sharing economy as an alternative model of consumption, one which seeks to increase the efficiency of the resources creating new value for societies. This new value is largely possible through the digital revolution providing previously inaccessible tools, through new quality in interpersonal relationships as well as increasing social awareness. The aim of the paper is to provide a systematic review of the literature and to clarify the principle of true sharing as opposed to a profit-based orientation.